Lightweight Investigation of Extended-Range Electric Vehicle Based on Collision Failure Using Numerical Simulation - Jiangqi Long; Wenhao Huang; Wuhu Zhang (Shock and Vibration)
The total weight of Extended-Range Electric Vehicle (E-REV) is too heavy, which affects rear-end collision safety. Using numerical simulation, a lightweight method is designed to reduce E-REV body and key parts weight based on rear-end collision failure analysis. To calculate and optimize the performance of vehicle safety, the simulation model of E-REV rear-end collision safety is built by using finite element analysis. Drive battery pack lightweight design method is analyzed and the bending mode and torsional mode of E-REV before and after lightweight are compared to evaluate E-REV rear-end collision safety performance. The simulation results of optimized E-REV safety structure are verified by both numerical simulation and experimental investigation of the entire vehicle crash test.